Teachers' collaboration in a mathematics lesson study - Ponte, João Pedro da (2020)
We aim to understand how primary teachers who participated in a lesson study developed their collaboration relationships. The research is qualitative and interpretive with a case study design. The results show that the involvement in moments of planning and analysis of the students’ work, where teachers reflected on practice and for practice helped them to develop collaborative relationships, moving from storytelling and scanning to joint work. The teachers were encouraged to express their voices regarding their participation in the lesson study and this led to an increasing involvement in the group, favoring the development of their reflection and knowledge of mathematics teaching.